Management of suspected and confirmed COVID‐19 (SARS‐CoV‐2) vaccine hypersensitivity. Issue 11 (4th July 2022) - Worm, Margitta; Alexiou, Aikaterina; Bauer, Andrea; Treudler, Regina; Wurpts, Gerda; Dickel, Heinrich; Buhl, Timo; Müller, Sabine; Jung, Andreas; Brehler, Randolf; Fluhr, Joachim; Klimek, Ludger; et al.
Abstract: Background: Systemic allergic reactions to vaccines are very rare. In this study we assessed the management and outcome of suspected SARS‐CoV‐2 vaccine hypersensitivity. Methods: Totally, 334 individuals underwent an allergy work up regarding SARS‐CoV‐2 vaccination (group A: 115 individuals suspected to be at increased risk for vaccine‐related reactions before vaccination and group B: 219 patients with reactions after COVID vaccination). The large majority of the SPT/IDT with the vaccines were negative; however, we identified in 14.1% ( n  = 47) a possible sensitization to the SARS‐CoV‐2 vaccine and/or its ingredients defined as one positive skin test. Of the 219 individuals (group B) who experienced symptoms suspicious for a hypersensitivity reaction after vaccination, 214 were reported after the first vaccination with a mRNA vaccine (157 mRNA (Comirnaty®, 38 Spikevax®) and 18 with a vector vaccine (Vaxzevria®), 5 cases were after the second vaccination. Results: The symptom profile in group B was as follows: skin symptoms occurred in 115 cases ( n  = 59 angioedema, n  = 50 generalized urticaria and n  = 23 erythema/flush. Seventy individuals had cardiovascular, 53 respiratory and 17 gastrointestinal symptoms. Of the overall 334 individuals, 78 patients tolerated (re)‐vaccination (out of skin test positive/negative 7/19 from group A and 17/35 from group B). Conclusion: Proven IgE‐mediated hypersensitivity to SARS‐CoV‐2 vaccines is extremely rare and not increased in comparison with reported hypersensitivity to other vaccines. The value of skin tests is unclear and nonspecific reactions, in particular when intradermal testing is applied, should be considered. Abstract : This study assesses the management and outcome of suspected SARS‐CoV‐2 vaccine hypersensitivity in 334 individuals who underwent an allergy work up. Of the 219 individuals who experienced symptoms suspicious for a hypersensitivity reaction after vaccination, 214 were reported after the first vaccination with a mRNA vaccine and 18 with a vector vaccine. Five cases were reported after the second vaccination. IgE‐mediated hypersensitivity to SARS‐CoV‐2 vaccines is extremely rare and not increased in comparison to the reported hypersensitivity rates for other vaccines.Abbreviations: COVID‐19, coronavirus disease 2019; SARS‐CoV‐2, severe acute respiratory syndrome coronavirus 2